Original paper Predictors of restenosis in patients treated with angioplasty for subclavian artery occlusive disease - Przewłocki, Tadeusz; Kabłak-Ziembicka, Anna; Pieniążek, Piotr; Musiałek, Piotr; Kozanecki, Artur; Rosławiecka, Agnieszka; Zalewski, Jarosław; Żmudka, Krzysztof; Tracz, Wiesława (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2009)
Background: Subclavian angioplasty (PTA) is widely used in the treatment of subclavian (SAS) and innominate (IAS) artery obstruction, however factors influencing long-term outcome are not well determined. Aim: To assess incidences and predictors of restenosis after SAS/IAS PTA. Methods: PTA was attempted in 168 (73 M) patients, aged 61.6 ± 8.3 years with angiographically confirmed SAS/IAS ł 50%, and symptoms of cerebral ischemia, upper limb claudication, subclavian-coronary steal or for obtaining blood pressure control. Results: PTA was successful in 159 (94.6%) patients and 164 lesions; including 141 (100%) stenotic lesions and 23 (71.9%) out of 32 occlusions. Mean stenosis grade was reduced from 75.7 ± 15.7% to 12.3 ± 10.9% (p < 0.01). Balloon angioplasty was performed in 11 (6.9%), single stent was implanted in 134 (84,3%), and 2 stents within one lesion in 14 (8,8%) patients. Complete symptom resolution was observed in 90.6% of patients after successful PTA. A 6 months follow-up period was completed by 151 patients (44.7 ± 19.6 months). Twenty-one (13.9%) restenoses ł 50% occurred, including 1 (9.1%) out of 11 after balloon angioplasty, 15 (11.8%) out of 127 after one stent implantation, and 5 (38.5%) after 2 stents implantation for one lesion (p = 0.029). Nineteen symptomatic restenoses were successfully treated with repeated angioplasty. Multivariable analysis revealed that independent predictors of restenosis were implantation of 2 stents (p = 0.046), smaller stent diameter (p = 0.029), and increased hs-CRP level (p < 0.001). A trend to association with younger age was observed (p = 0.06). Conclusions: Angioplasty is a safe and effective method for the treatment SAS/IAS and leads to symptom reversal in majority of patients. Hs-CRP level, stent diameter, 2 stents implanted for one lesion are independent predictors of restenosis.